2017
DOI: 10.1002/jcp.25785
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of autophagy and apoptosis: Involvement of the dual role of autophagy under ER stress

Abstract: Endoplasmic reticulum (ER) stress is a common cellular stress response that is triggered by a variety of conditions that disturb cellular homeostasis, and induces cell apoptosis. Autophagy, an important and evolutionarily conserved mechanism for maintaining cellular homeostasis, is closely related to the apoptosis induced by ER stress. There are common upstream signaling pathways between autophagy and apoptosis induced by ER stress, including PERK/ATF4, IRE1α, ATF6, and Ca . Autophagy can not only block the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
296
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(311 citation statements)
references
References 46 publications
14
296
0
1
Order By: Relevance
“…The inability of cells to remove damaged proteins from the ER for a prolonged period of time triggers an apoptotic cell death pathway (Hiramatsu et al, 2015;Song et al, 2017). A similar observation was made in vitro when cells were exposed to high levels of oxidised amino acids to generate oxidised proteins (Dunlop et al, 2008) suggesting that oxidised proteins can also trigger apoptotic cell death in a similar way.…”
Section: Discussionsupporting
confidence: 50%
“…The inability of cells to remove damaged proteins from the ER for a prolonged period of time triggers an apoptotic cell death pathway (Hiramatsu et al, 2015;Song et al, 2017). A similar observation was made in vitro when cells were exposed to high levels of oxidised amino acids to generate oxidised proteins (Dunlop et al, 2008) suggesting that oxidised proteins can also trigger apoptotic cell death in a similar way.…”
Section: Discussionsupporting
confidence: 50%
“…Due to oxidative stress reactions in IRI, the increasing intracellular ROS level stimulates mitochondria-mediated apoptosis. Caspase-8 and caspase-9 are two important indicators of mitochondria-mediated apoptosis [51, 52], and our results showed that RSV downregulated both factors in vivo and in vitro , indicating that RSV reduced cell apoptosis by downregulating the caspase cascade. The caspase cascade also includes another effector, caspase-3, which can be activated in IRI and directly mediates cell apoptosis.…”
Section: Discussionmentioning
confidence: 80%
“…Generally, autophagy blocks the induction of apoptosis and inhibits the activation of apoptosis‐associated caspase which could reduce cellular injury 45. However, in special cases, autophagy or autophagy‐relevant proteins may help to induce apoptosis, which could aggravate cell damage 46. Therefore, it is not surprising that many scholars have drawn opposite conclusions about the role of autophagy in various acute injuries.…”
Section: Discussionmentioning
confidence: 99%